2008
DOI: 10.1103/physrevlett.100.056807
|View full text |Cite
|
Sign up to set email alerts
|

Periodically Rippled Graphene: Growth and Spatially Resolved Electronic Structure

Abstract: We grow epitaxial graphene monolayers on Ru(0001) that cover uniformly the substrate over lateral distances larger than several microns. The weakly coupled graphene monolayer is periodically rippled and it shows charge inhomogeneities in the charge distribution. Real space measurements by scanning tunneling spectroscopy reveal the existence of electron pockets at the higher parts of the ripples, as predicted by a simple theoretical model. We also visualize the geometric and electronic structure of edges of gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
267
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 592 publications
(290 citation statements)
references
References 23 publications
14
267
3
Order By: Relevance
“…The growth of large‐area high‐quality graphene films is fundamental for the upcoming graphene applications. Chemical vapour deposition (CVD) method offers good prospects to produce large‐size graphene films due to its simplicity, controllability and cost‐efficiency 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75. Many researches have verified that graphene can be catalytically grown on metallic substrates, like ruthenium (Ru),13, 14 iridium (Ir),15, 16 platinum (Pt),17, 18, …”
Section: Introductionmentioning
confidence: 99%
“…The growth of large‐area high‐quality graphene films is fundamental for the upcoming graphene applications. Chemical vapour deposition (CVD) method offers good prospects to produce large‐size graphene films due to its simplicity, controllability and cost‐efficiency 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75. Many researches have verified that graphene can be catalytically grown on metallic substrates, like ruthenium (Ru),13, 14 iridium (Ir),15, 16 platinum (Pt),17, 18, …”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models of ripples in graphene suggest that the resulting local surface curvatures affect the microscopic parameters of the electronic states such as hopping matrix elements and the coupled dispersion relations. In addition to changing microscopic parameters and creating local effects such as strong pseudomagnetic fields 19 , structural ripples can also result in an added periodic potential 20 in the energy landscape. The effects of such periodic potentials on the electronic structure of graphene have been extensively explored theoretically [21][22][23][24][25] where it was shown that periodic potentials may not only change band parameters similar to the Fermi velocity but also induce additional zero energy modes and bandgaps.…”
mentioning
confidence: 99%
“…Graphene ripples less than 1 nm high, for example, have been shown to cause spatial charge redistribution [3,4] and electron scattering [5], to enhance graphene's chemical reactivity [6,7], and affect its thermal stability [8,9]. Aiming for high-quality graphene electronics, the search for suitable substrates has increasingly focused on layered materials, like mica [10], hexagonal boron nitride (h-BN) [11], or MoS 2 [12].…”
Section: Introductionmentioning
confidence: 99%